Investigation of the regulation of the CBP20 gene in Arabidopsis - Bacsó, Renáta; Papp, István (Acta Biologica Szegediensis, 2008)
Changes of the activity of antioxidative enzymes (APX, GPX) were investigated in barley roots and leaves during a one day and a one week setting of 0, 100, 500, 1000 μM nickel treatment parallel with the measurement of nickel accumulation in order to elucidate the mechanisms in terms of anitoxidative enzyme activity during the early phase of nickel exposure. We concluded that nickel also cause ROS formation in barely seedlings in the roots and also in the leaves. In the inactivation of ROS both APX and GPX play role although to different extent and for different duration. Moreover APX reacts rapidly to nickel stress, since its activity rises even after three hours of the nickel treatment.